Modulation of relapse-like drinking in male Sprague-Dawley rats by ligands targeting the α5GABAA receptor. (1st November 2021) - Chandler, Cassie M.; Reeves-Darby, Jaren; Jones, Sherman A.; Li, Guanguan; Rahman, Md T.; Cook, James M.; Platt, Donna M.
Abstract: Preclinical evidence suggests a key role for GABAA receptors containing the α5 subunit (i.e., α5GABAA receptors) in the abuse-related effects of alcohol, including the reinforcing and discriminative stimulus effects, as well as cue-induced alcohol-seeking behavior. However, the contribution of this GABAA receptor subtype to relapse-like drinking behavior remains unknown. The present study evaluated the capacity of ligands targeting α5GABAA receptors to modulate the alcohol deprivation effect (ADE), a model of relapse-like drinking. Groups of Sprague-Dawley rats underwent repeated cycles of long-term access to alcohol solutions (5%, 10%, 20% v/v) and water in the home cage followed by water only deprivation periods. Upon evidence that the ADE could be reliably expressed across cycles, drug treatment was initiated. One group received the α5GABAA receptor-preferring agonist QH-ii-066 and the other group received the α5GABAA receptor-selective inverse agonist L-655, 708. At the end of ADE testing, rats underwent testing in the elevated zero maze under vehicle or L-655, 708 treatment for assessment of anxiety-like behavior. The ADE was reliably expressed across repeated cycles of alcohol access/deprivation in a subset of rats. Low doses of QH-ii-066 enhanced expression of the ADE; whereas, L-655, 708 dose-dependently inhibited expression of the ADE. L-655, 708 did not engender anxiogenic effects in the elevated zero maze under the conditions evaluated. These findings suggest a key role for α5GABAA receptor mechanisms in relapse-like drinking. Moreover, they suggest that α5GABAA receptors may represent a novel pharmacological target for the development of medications to prevent or reduce alcohol relapse. Highlights: The alcohol deprivation effect (ADE) is a model of relapse-like drinking. α5GABAA agonists augment, and α5GABAA inverse agonists attenuate, the ADE. α5GABAA receptors are key mediators of alcohol relapse. α5GABAA inverse agonists may be useful therapeutics for alcohol use disorders.